Characteristics of Metal–Semiconductor–Metal Ultraviolet Photodetectors Based on Pure ZnO/Amorphous IGZO Thin-Film Structures. (12th April 2021) - Lam, Kin-Tak; Young, Sheng-Joue; Chu, Yen-Lin; Tsai, Chi-Nan; Chu, Tung-Te; Lu, Ting-Sung; Ji, Liang-Wen
Abstract : In this study, metal–semiconductor–metal-structured ultraviolet (UV) photodetectors (PDs) based on pure zinc oxide (ZnO) and amorphous indium gallium zinc oxide (a-IGZO) thin films were fabricated and characterized. The ZnO seed layers were deposited on Corning glass substrates via a radio frequency (RF) magnetron sputtering technique. Results showed that under a 5 V applied bias; the dark currents of the pure ZnO and a-IGZO thin films were 0.112 pA and 2.85 nA, respectively. Meanwhile, the UV-to-visible rejection ratio of the pure ZnO and a-IGZO thin films were 14.33 and 256, respectively. Lastly, the PDs of thea-IGZO thin films had a lower leakage current and higher rejection ratio than that of the pure ZnO thin films from the UV to visible light region.